Thymoma: A Comprehensive Review of this Indolent Anterior Mediastinal Tumor - Kumawat, Manoj Kumar; Sharma, Neeti; lal Jakhar, Shankar; Kumar, H. S.; Kumar, Rajesh (Asian Pacific Journal of Cancer Care, 2024)
Thymic tumors, including thymoma and thymic carcinoma, represent a diverse group of malignancies with variable clinical presentations. Despite their rarity, thymoma remains a significant clinical entity due to its potential for local invasion and recurrence. Approximately 50% of thymomas are diagnosed incidentally during chest radiography. This review provided a comprehensive overview of thymoma, encompassing its classification, clinical features, diagnosis, treatment, and prognosis. Various staging systems and their impact on management decisions were also discussed. Thymectomy, the primary treatment for thymoma, was explored in detail, along with the role of adjuvant therapies. Furthermore, a case study of a 20-year-old male who presented with shortness of breath, cough, chest pain, and fever was focused. Imaging revealed mediastinal widening and right-sided pleural effusion, leading to a diagnosis of lymphocytic-rich type B thymoma following fine needle aspiration and biopsy. This case highlighted the clinical presentation and diagnostic approach to thymoma.